Women in the printing trades, 1918 (1918)
1918 1918-1939 "Women in the printing trades, 1918" [EP0055], 1918 This letter from the National Society of Operative Printers and Assistants to Margaret Postgate [later Cole ] at the Fabian Research Department, dated 12 January, 1918, reports on the position of women in the printing trade as regards equal pay and rates of wages generally. The letter is from the Labour Research Department Archive.